Incidencia del virus Herpes simplex en pacientes con infecciones agudas del sistema nervioso central - Pérez S Kriss; Porto-Espinoza Leticia; Mindiola Raimy; Callejas M Diana; Estévez Jesús; Moronta, Reyna (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Abstract: Herpes simplex viruses are agents responsible for a variety of infections on buccal and genital mucosa; they are neurotropic, capable of lodging in the nerve cells and remaining latent with subsequent reactivations; in some cases, they can provoke meningitis and encephalitis; and they have a significant morbidity and are associated with a high mortality. The present project aims to determine HSV's effect on the etiology of acute central nervous system (CNS) syndromes using the detection of specific antibodies in serum and cerebrospinal fluid. The 93 paired samples from patients with neurological affectations studied demonstrated negative results in the LCR bacteriological study and their Alb-LCR/Alb-serum relation was < 0.0075. Antibodies were detected by the enzymatic immunoassay ELISA method, where 1.2% (1/93) of the serum samples turned out positive for IgM; 89.24% (83/93) of the serum samples resulted positive for IgG; and 27.39% (20/93) of LCR samples were positive for anti-IgG. IgG presence in LCR suggested the intrathecal production of these antibodies inside the CNS, which demonstrates a significant participation by this viral agent in infections and diseases associated with the CNS. Resumen: Los Virus Herpes Simple son responsables de una variedad de infecciones a nivel de mucosas bucal y genital, son neurotrópicos, capaces de alojarse en células nerviosas y permanecer latentes con subsecuentes reactivaciones, en algunos casos pueden provocar meningitis y encefalitis. tienen una morbilidad significativa y una mortalidad elevada. El presente estudio tiene como objetivo determinar la incidencia de VHS en la etiología de los síndromes agudos del SNC mediante la detección en suero y LCR de anticuerpos específicos. Se estudiaron 93 muestras pareadas de pacientes con afecciones neurológicas que mostraron resultados negativos en el estudio bacteriológico de LCR y cuya relación Alb-LCR/Alb-suero fue <0,0075. Los anticuerpos fueron detectados por el método de inmunoensayo enzimático Elisa: Enzygnost anti virus VHS/IgM-IgG (Behring, 1994), donde 1,2% (1/93) de las muestras de suero resultaron positivas para IgM; 89,24% (83/93) de los sueros resultaron positivos para IgG; y 27,39% (20/93) de las muestras de LCR presentaron anti-IgG positivo. La presencia de IgG en LCR sugiere la producción intratecal de estos anticuerpos en el SNC, lo que muestra una participación importante de este agente viral en las infecciones y enfermedades asociadas al SNC.